Schrödinger's Cat—Parallel experiences: exploring the underlying mechanisms of undergraduates' engagement and perception in online learning - Zhang, Hongfeng; Liu, Yan; Su, Shaodan (Frontiers in Psychology, 2024)
Based on the learning experiences of undergraduates, this study explores the underlying occurrence mechanisms and connotations of interrelations and influence of various phenomena in online learning. The study adopts The Grounded Theory approach, including three-level coding, constant comparison method, theoretical sampling, core category extraction, and storyline development, to construct a substantive theoretical model. The results show that online features lead to students' motivation mainly depending on self-regulated levels. Teacher-student interactions and self-regulation shape different learning contexts and types by being moderated by internal and external effects. However, students with different engagement had a parallel experience similar to that of Schrödinger's Cat: they were constantly dissatisfied with "rational" learning and "perceptually" satisfied with online learning. The study found that the basic psychological needs of autonomy, relatedness, and competence, proposed by self-determination theory, play a crucial role in this context. The variation in the satisfaction of the three basic needs of college students in online learning leads to parallel experiences. The students' learning engagement and experience result from a combined influence of self-determination and natural determination. The findings provide a more profound basis for theoretical development and educational improvement of online learning.